A commentary on Exodus - Garrett, Duane A.; Garrett Duane A. (Grand Rapids : Kregel, 2014)
The true fountainhead of Old Testament theology, Exodus illuminates the significance of the name Yahweh and introduces the title I AM. It tells of Israel's formative historical event, the exodus, as well as the making of the covenant at Sinai. It includes the first code of the Law in the Decalogue and Book of the Covenant. It details Israel's besetting sin in the idolatry of the golden calf episode, but it also describes Moses's intercession and the great revelation of God's mercy. In its display of the Tent of Meeting, it presents the theology of the priesthood, the sacrifices, and the central sanctuary. A Commentary on Exodus explores all of these events with a view toward their significance both for the meaning of the Old Testament and for the message of the Christian church. Exegetically deep enough to satisfy the scholar and logically organized to meet the needs of the pastor, Garrett's commentary promises to become standard reference material in Exodus studies. - See more at: http://www.kregel.com/bible-commentaries/a-commentary-on-exodus/#sthash.uyzdeYNd.0EjlsY5F.dpuf
Until Moses (1:1-2:10) -- An unlikely savior (2:11-7:7) -- The twelve miracles of the Exodus (7:8-15:21) -- The journey to God (15:22-19:25) -- The Sinai covenant (20:1-24:11) -- The worship of God (24:12-31:18) -- Sin and restoration (32:1-40:38) -- Appendix: the songs of Exodus.
Includes bibliographical references (pages 723-741).
Keywords: Bible. -- Commentaries; Commentaries